THE IMPROVEMENT OF TECHNOLOGICAL PROCESS AND EQUIPMENT FOR PRODUCTION OF CASTINGS OF THE INTERNAL COMBUSTION ENGINES PISTON RINGS - A. P. Melnikov (Литьë и металлургия)
The competitive technology is developed on the basis of theoretical and experimental investigations carried out in OAO “BELNIILIT” and new moulding equipment which found application at many enterprises of the far and the near abroad and only in China.